(3QSGdI QLd MGL Edi GdSdWGf SYO Hf RjO TQja ecI Jhdi YGe (B1077 (3g`s
(3ChdgG (B:s
(3ef YHOGddg ESeGYjd Hf Ydi Hf Edi ef JMdJ GdCjGe HeMGSf Tjeg GdSdWGf SYO Hf GdSdWGf RjO s
(3BNQgG (B:s
(3abO MedJfG eMHI Pdc GdMQe GdTQja Ydi JPcQJc hfUjMJc hbO YhOfG Gddg GdJPcQI hGdfUjMI dLejY ef YQafG ef GdeSdejf hhLOfG s
(3HgG JeRjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B196 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs